Where is the greatest risk of COVID-19 infection? Findings from Germany's largest public health department, Cologne. - Lukas Broichhaus; Julian Book; Sven Feddern; Barbara Grüne; Florian Neuhann; Johannes Nießen; Gerhard A Wiesmüller; Annelene Kossow; Christine Joisten (PLoS ONE, 2022)
Background SARS-CoV-2 has been spreading worldwide since late 2019. Before vaccines became available, exclusively non-pharmaceutical measures were used to prevent transmission of infection. Despite the fact that vaccinations are now available, it is still important to identify relevant transmission routes in order to contain the COVID-19- or further pandemics. Therefore, this study aims to systematically analyse data from the largest public health department in Germany to determine the significance of the various known and unknown transmission situations in terms of the proportion of infections. Methods All infections in Cologne were systematically recorded by the local health department. In addition to clinical data, the transmission situations were recorded and categorised as pertaining to social contact, work contact, travellers, health care workers, users of educational institutions, visitors of community institutions, infection in the context of medical treatment, and unknown infection. Findings The analysis included 25,966 persons. A transmission situation could be identified in 82.7% of the cases (n = 21,477). Most persons (42.1%) were infected due to social contact, primarily within their own household. Another 22.3% were infected at their place of work; this was particularly common among staff members of medical facilities, nursing homes and educational institutions. In 17.3% of the cases, the transmission situation remained unknown; the cases with unknown transmission situation were slightly more often symptomatic (75.2%) than the cases with known transmission situation (69.4%). Interpretation Considering that during the study period the leading strains were the wild-type and alpha-variant transmission rather occurred during scenarios involving close contacts than in anonymous situations. Presumably, however, the findings can be transferred to the new variants. Therefore, in order to prevent transmission, besides vaccination regular antigen tests and/or appropriate protective measures remain relevant until this pandemic has subsided.